1983
DOI: 10.1093/infdis/148.3.563
|View full text |Cite
|
Sign up to set email alerts
|

Intraphagocytic Killing of Salmonella typhimurium by Liposome-Encapsulated Cephalothin

Abstract: Multilamellar liposomes (lipid bilayer vesicles) composed of phosphatidylcholine, cholesterol, and phosphatidylserine (molar ratio, 6:3:1) were produced and then made to entrap an aqueous solution of cephalothin. Resident murine peritoneal macrophages were shown to be capable of interiorizing the liposome-antibiotic complex; this event resulted in a relatively high intracellular concentration of cephalothin. In macrophages infected in vitro with Salmonella typhimurium, intracellular killing of the bacteria was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…Therefore, as indicated by Desiderio and Campbell (1983) and also by our results, infections of these bacteria may be favorably treated with these antibiotics if they are administered in liposomeencapsulated forms. This administration method, if proved effective also in vivo, is expected to provide valuable alternatives for the treatment of intracellular bacterial infections.…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, as indicated by Desiderio and Campbell (1983) and also by our results, infections of these bacteria may be favorably treated with these antibiotics if they are administered in liposomeencapsulated forms. This administration method, if proved effective also in vivo, is expected to provide valuable alternatives for the treatment of intracellular bacterial infections.…”
Section: Discussionsupporting
confidence: 66%
“…Liposome formulations of these antibiotics may improve pharmacokinetics and also the targeted delivery to the intracellular infections. In a study with cephalotin, treatment of infected macrophages with multilamellar liposomeencapsulated cephalothin enhanced the intraphagocytic killing of Salmonella typhimurium over that by macrophages treated with free cephalothin (54). Resident murine peritoneal macrophages were shown to be capable of interiorizing the liposome-antibiotic complex leading to a relatively high intracellular concentration of cephalothin.…”
Section: Cephalosporine Loaded Liposomesmentioning
confidence: 99%
“…Liposome-encapsulated antibiotics have been shown to have improved penetration into phagocytic cells and have been advocated for use against intracellular microbes (1,22). Indeed, this carrier system augmented the efficacy of various antimicrobial agents against a wide range of microorganisms that survive within macrophages (1,6,9,25). Our laboratory -has previously reported that the use of cefoxitin encapsulated within unilamellar liposomes (95% dipalmitoylphosphatidylcholine, 5% phosphatidylserine) significantly reduced the mortality rate compared with that with the use of free cefoxitin in an intra-abdominal infection model in the rat (5).…”
mentioning
confidence: 99%
“…3B. Liposomal encapsulation of antimicrobial agents has proven to be an effective means of drug delivery, particularly against intracellular pathogens (1,9). Phagocytic uptake of liposomes facilitates-exposure of these microorganisms to concentrations of drug which are not normally achieved by incubation of cells with the free antibiotic and results in enhanced microbial killing (25).…”
mentioning
confidence: 99%